THE INFLUENCE OF DIGITAL MARKETING AND ELECTRONIC WORD OF MOUTH ON PURCHASING DECISIONS THROUGH TRUST IN MATAHARI DEPARTMENT STORE PEKANBARU CITY CONSUMERS - Habibi, Yonanda (Universitas Negeri Yogyakarta, 2023)
This study was conducted with the aim of knowing the effect of digital marketing and electronic word of mouth on purchasing decisions of the Pekanbaru community at the Matahari Department Store through consumer confidence. The population in this study were Pekanbaru people who had shopped at Matahari Department Store in Pekanbaru City. Sampling in this study was carried out using purposive sampling technique using the Lemeshow formula, so that the number of samples in this study were 100 respondents. The data analysis method of this study uses the Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis method with SmartPLS software version 4.0.9.2. The results showed that there is a positive and significant influence between digital marketing on consumer trust. There is a positive and significant influence between electronic word of mouth on consumer trust. There is a positive and significant influence between digital marketing on purchasing decisions. There is a positive and significant influence between electronic word of mouth on purchasing decisions. There is a positive and significant influence between consumer confidence on purchasing decisions. There is a positive and significant influence between digital marketing on purchasing decisions through consumer confidence. There is a positive and significant influence between electronic word of mouth on purchasing decisions through trust.